Discuss the Impact of BIM on the Engineering Cost Industry in the Era of Big Data and the Countermeasures - Li, Sheng; He, Jiarong; Wang, Chunli (Journal of Theory and Practice of Engineering Science, 2023)
In the development process of the Big data era, all industries have begun to use new technical methods to carry out business activities to improve work quality and efficiency. In terms of the construction and development of the engineering cost industry, managers can use the BIM technology in the Big data era to solve problems in engineering cost management and improve the effectiveness of cost management. This paper mainly analyzes the factors that affect project cost and the impact of BIM on the project cost industry, and puts forward countermeasures to optimize the application effect of BIM technology in the construction of the project cost industry in the Big data era.